Analyzing Differences and Interrelations between Maqāṣid Al-Qur’ān and Maqāṣid Al-Sharī‘ah - Ahmad Anas; Afaful Ummah; Fasjud Syukroni (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2025)
This research addresses a persistent conceptual gap in the fields of Qur'anic exegesis (tafsīr) and Islamic legal theory, namely the overlap and lack of systematic distinction between maqāṣid al-Qur'ān (the objectives of the Qur'an) and maqāṣid al-sharī‘ah (the objectives of Islamic law). Although both concepts are increasingly referenced in contemporary Islamic discourse—alongside the development of tafsīr maqāṣidī (purpose-based exegesis)—the theoretical boundaries, developmental genealogy, and methodological relationship between the two remain under-theorized in existing literature. This study presents a novel analytical comparison by examining both frameworks through six dimensions: definition, source, methodological approach, historical development, axiology, and operational function. Through a comparative-analytical qualitative study of classical and contemporary sources, this paper demonstrates that the relationship between the two is one of absolute generality and specificity (al-‘umūm wa al-khuṣūṣ al-muṭlaq), wherein every maqāṣid al-sharī‘ah is encompassed within the maqāṣid al-Qur’ān, but the reverse is not true. Furthermore, this research clarifies that tafsīr maqāṣidī functions as an interpretive tool (wasīlah) to uncover maqāṣid al-Qur’ān, particularly at the thematic, verse, and surah levels. By proposing this clearer typology and hierarchical model, this research contributes to a more precise and methodologically grounded application in Qur'anic interpretation, Islamic legal theory, and contemporary ijtihād.